Outcomes in resident‐performed cataract surgeries with iris challenges: Results from the Perioperative Care for Intraocular Lens study. Issue 12 (December 2018) - Moustafa, Giannis A.; Borkar, Durga S.; McKay, Matthew K.; Eton, Emily A.; Koulisis, Nicole; Lorch, Alice C.; Kloek, Carolyn E.
Abstract : Purpose : To assess the outcomes of resident‐performed cataract surgeries with iris challenges and to compare these outcomes with similar surgeries performed by attending surgeons. Setting : Massachusetts Eye and Ear Infirmary, Harvard Medical School, Boston, Massachusetts, USA. Design : Retrospective chart review. Methods : All cases of cataract extraction by phacoemulsification with intraocular lens implantation, performed by comprehensive ophthalmologists between January 1 and December 31, 2014, were reviewed. Cases with preoperative or intraoperative miosis, iris prolapse, and intraoperative floppy iris syndrome, were included for analysis. Visual outcomes and the rate of perioperative adverse events were compared between resident and attending surgeon cases. Factors predicting adverse events were also assessed. Results : In total, 1931 eye cases of 1434 patients were reviewed, and 65 resident cases and 168 attending surgeon cases were included. The mean logarithm of the minimum angle of resolution corrected distance visual acuity was better in the resident group 1 month after surgery (0.051 ± 0.10 [SD] versus 0.132 ± 0.30, P = .03); however, the difference was eliminated when controlling for macular disease. The mean operative time was 43.8 ± 26.5 minutes and 30.9 ± 12.6 minutes for cases performed by resident surgeons and attending surgeons, respectively ( P .0001). Residents utilized supplemental pharmacologic dilation or retraction more frequently than attending surgeons (98% versus 87% of cases, P = .008). The overall rate of adverse events was no different between residents and attending surgeons ( P = 0.16). Dense nuclear sclerosis predicted adverse events in cataract cases with iris challenges (adjusted odds ratio, 1.86; 95% confidence interval, 1.17–2.94; P = .001). Conclusion : Although requiring longer operative times and more surgical manipulation, residents who performed cataract surgeries with iris challenges achieved outcomes comparable to those performed by attending surgeons, and residents should be given the opportunity to operate on these eyes.